Evaluation of contaminants in agricultural soils in an irrigation district in Colombia (2019)
This study evaluated the concentration and distribution of heavy metals (HM) (Cr, Ni, Pb, Cd, Hg, and Zn) and pesticides (organochlorine and organophosphorus) and the relationship of these pollutants with the physicochemical properties of agricultural soils in an Irrigation District (ID) in Colombia. Soils samples were analyzed for pH, humidity, organic matter, P total, N total, electric conductivity (EC), cation exchange capacity, and texture (% sand, clay and silt). Canonical correlation was used to determined relationship between soil properties and HM. Soil pollution were evaluated with geoaccumulation index (Igeo), contamination factor (CF), degree of contamination (Cdeg) and pollution load index (PLI). The results indicated that, in general, the soils had adequate physicochemical conditions for the establishment and development of crops. The presence of pesticides in the soils was not reported. However, concentrations HM was detected (Zn > Cr > Ni > Pb > Hg > Cd). The soil characteristics (silt, clay, pH and EC) contributed to explain HM concentrations. The Igeo indicated that the soils are heavily contaminated with Hg (3 < Igeo<4). The CF was very high for Hg (>6). The Cdeg presented moderate to considerable variations (>6Cdeg<24). The PLI indicated that the soils are contaminated (1.308). The presence of HM may be associated with the agricultural and quarries activities carried out near the ID. The impact caused by high concentrations of HM can lead environmental, economic and social impacts in the study zone.